2007
DOI: 10.1111/j.1600-0668.2007.00499.x
|View full text |Cite
|
Sign up to set email alerts
|

Location identification for indoor instantaneous point contaminant source by probability-based inverse Computational Fluid Dynamics modeling

Abstract: Practical ImplicationsThe method developed can help track indoor contaminant source location with limited sensor outputs. This will ensure an effective and prompt execution of building control strategies and thus achieve a healthy and safe indoor environment. The method can also assist the design of optimal sensor networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(34 citation statements)
references
References 7 publications
1
33
0
Order By: Relevance
“…Cough aerosols were initially carried in a plume capable of http://dx.doi.org/10.1016/j.enbuild.2014. 10.014 0378-7788/© 2014 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Cough aerosols were initially carried in a plume capable of http://dx.doi.org/10.1016/j.enbuild.2014. 10.014 0378-7788/© 2014 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 98%
“…Computational fluid dynamics (CFD) simulation tools have been frequently utilised for the simulation of the transportation of contaminants with ventilation flows [8][9][10][11][12]. These studies are capable of indicating various factors responsible for aerosol dispersion, as well as examining the source and airflow characteristics of the room that are driven by ventilation and temperature gradients.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that a grid number of 1.2×10 5 is appropriate for obtaining reasonably gridindependent solutions for this case, which thus was used for the following simulations. Figure 3 shows the simulated airflow field in the cabin, which was validated against physical experiment results (Liu and Zhai 2007b). Figure 4 presents the simulated dynamic contaminant concentration readings at the two sensor locations during the first 100 seconds after the contaminant was released.…”
Section: Fig 3 Aircraft Cabin Cfd Model Simulated Main Airflows Anmentioning
confidence: 99%
“…Although Wang et al (2013) developed an original method to identify an unknown point source in steady-state flow and concentration field, the method is only applicable to identification of single point source. The probability-based CFD modeling which uses the results of CFD calculation for all the potential point sources has the same limitation though the method could identify the source location with very high accuracy by using the limited number of sensor(s) (Liu and Zhai 2008). Assuming that the potential locations of source(s) are limited, rapid identification of the source location(s) can be performed by using the limited number of sensors (Cai et al 2012(Cai et al , 2014.…”
Section: Introductionmentioning
confidence: 99%